OPTIMIZING THE COMPETENCE AND PROFESSIONALISM OF ACCOUNTING TEACHERS IN USING ACCURATE SOFTWARE: Optimalisasi Kompetensi dan Profesionalisme Guru Akuntansi Dalam Menggunakan Software Accurate - Rahayu, Ruci Arizanda; Abidin, Fityan Izza Noor; Pebrianggara, Alshaf; Milasari, Anis (Antis-publisher, 2024)
Based on the observations made, problems were found including accounting records that were still manual and a lack of understanding regarding accurate software. The lack of expertise in the use of technology in the accounting process creates a new problem, which is difficult to get a decent job for job seekers. Among job seekers, there are various educational backgrounds, ranging from high school graduates, vocational schools, as well as undergraduate graduates from various universities. The Muhammadiyah Sidoarjo University Community Service Center conducts training on Accurate accounting software for teachers and vocational students in Sidoarjo. Training is provided using Accurate software. The purpose of this training is to provide training to teachers and students in understanding and operating various features in Accurate related to transaction accounting which are expected to improve skills in using this software. The method in this service uses the PAR method which involves the teacher. The stages of implementing community service use the PAR method, namely initial mapping, implementation, and monitoring/evaluation. The results of the service carried out at the Muhammadiyah University of Sidoarjo went smoothly and the teachers succeeded in increasing teachers' understanding in using accurate applications.